Evaluasi Pengelolaan Sampah Ikan di Pasar Jembatan Puri Kelurahan Klaligi Kota Sorong - Melisa, Melisa; Purnomo, Arie; Muhdar, Aswad; Nurjannah, Siti (Universitas Muhammadiyah Sorong, 2024)
This research aims to describe and analyze the evaluation of fish waste management at the Jembatan Puri Market, Klaligi Village, Sorong City. In this research the author uses the concepts of waste management, waste impacts, fish waste management, and market management. This research uses a descriptive qualitative approach. The data collection techniques were carried out through observation, interviews, and literature review. With the following research results: First, the level of cleanliness and orderliness in the Jembatan Puri fish market, Klaligi Village, Sorong City may currently experience significant changes compared to several years ago, especially in terms of waste management. Second, the government's role in providing information, technical support, and resources to manage organic waste and control vector populations is very important. Environmental cleanup programs, health education, and training on waste management can help increase public awareness and encourage active participation in disease prevention efforts. Third, at the Jembatan Puri Fish Market, concrete steps have been taken to overcome the problem of waste management. One of the things that is done is to provide adequate and separate waste disposal sites according to type.